The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsomega.2c01891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tellurium Doping on Environmental Stability and Luminous Performance of CsPbBr3 Quantum Dots

Abstract: The effects of elemental tellurium doping and decorating on the photoluminescence quantum yield (PL QY) and the environmental stability of the CsPbBr 3 quantum dots (QDs) have been systematically studied. The PL spectra blue-shifts from 520 to 464 nm gradually with the increase in the amount of Te, and the full width at half-maximum (FWHM) increases from 20 to 62 nm and decreases to 27 nm accordingly. The morphology of the untreated samples has a rectangular shape with distinct boundarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Both types of devices were subjected to various stability tests including storage in a N 2 environment for 2000 h, continuous exposure to ultraviolet lamps for 300 min, and preservation at approximately 45% air humidity for 40 h. The stability test results clearly showed that the doped device had superior stability [85]. Apart from halogen doping with X elements, the stability of MHPs was also reported to improve through the doping of X elements from Group VI, such as sulfur (S), tellurium (Te), and other similar elements [89].…”
Section: Compositionmentioning
confidence: 99%
“…Both types of devices were subjected to various stability tests including storage in a N 2 environment for 2000 h, continuous exposure to ultraviolet lamps for 300 min, and preservation at approximately 45% air humidity for 40 h. The stability test results clearly showed that the doped device had superior stability [85]. Apart from halogen doping with X elements, the stability of MHPs was also reported to improve through the doping of X elements from Group VI, such as sulfur (S), tellurium (Te), and other similar elements [89].…”
Section: Compositionmentioning
confidence: 99%